The International Words in the Balkan Linguistic Area - PaÃ§o, Eliana (Mediterranean Journal of Social Sciences, 2012)
In our research, on the basis of Albanian words (of the Dictionary 1980) with the letters A and B in confrontation with above-mentioned languages a statistic analyses is carried out for the words of more or less affinity and in their differences on phonetic, phonologic, morphologic and word-formation levels.